Magnetic Nanoparticles For Enhanced Oil Recovery (Eor) Using Em Methods - Fathehah Bt Mohamad Azman, Fathehah (Universiti Teknologi Petronas, 2010)
Nickel nitrate, zinc nitrate and iron nitrate were used to synthesize nanosize nickel zinc ferrite (Ni0_8Zn0.2Fe2O4). The synthesis of nickel zinc ferrite has been extensively investigated in recent years because of their favorable properties such as high resistivity, low eddy current losses and high saturation magnetization [']' Therefore, it plays an important role in many technological applications, such as high density magnetic recording media and electromagnetic wave absorption materials [2].